Impacto nas emissões de gases de efeito estufa do setor de energia em Sergipe - Santos, Marcos Felipe Sobral dos (2024)
This study addresses the analysis of greenhouse gas (GHG) emissions in the energy sector of Sergipe, highlighting the significant impacts of these emissions in the regional context. The research was based on data from the Greenhouse Gas Emissions and Removals Estimation System (SEEG) and complemented by information from the National Electric Energy Agency (ANEEL). It was identified that, in 2021, the energy sector in Sergipe contributed 3.02 million tons of CO2 equivalent (CO2e), with the combustion of fossil fuels being the main source of emissions. The detailed analysis included the main gases involved, their emission sources, and the potential for mitigation through the use of renewable technologies. This study reinforces the importance of continuous monitoring and the implementation of effective policies to reduce GHG emissions, contributing to sustainable development in Sergipe.